2005
DOI: 10.1097/01.hjr.0000166455.23346.a5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-frequency electrical myostimulation and conventional aerobic exercise training in patients with chronic heart failure

Abstract: In patients with moderate to severe CHF, 5 weeks of EMS and conventional exercise training produce similar improvements to exercise capacity and muscle performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 40 publications
0
22
0
2
Order By: Relevance
“…Treatment of the patients with CHF through FES training has been proposed as an interesting alternative to CA. Other studies were published in the following years, but generally lacked sufficient power to provide a conclusive answer [10,14,15,21]. The first relevant study in the field was conducted by Harris et al [12], who compared conventional training with FES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of the patients with CHF through FES training has been proposed as an interesting alternative to CA. Other studies were published in the following years, but generally lacked sufficient power to provide a conclusive answer [10,14,15,21]. The first relevant study in the field was conducted by Harris et al [12], who compared conventional training with FES.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the impossibility of blinding patients and therapists in FES studies, it is possible to blind the evaluation of outcome, which occurred in only three studies [11,14,15]. Deley et al [14] 12/12 56 ± 8/57 ± 6 9/11 9-3-0 Moreover, two studies [10,21] also failed to describe the losses and exclusions that occurred during the treatment period [18,24]. Only the study carried out by Nuhr et al [9] described randomization to be based on a sealed envelope randomization list.…”
Section: Discussionmentioning
confidence: 99%
“…Maximizing the torque output generated by electrical stimulation is critical, especially when the goals are to achieve muscle strengthening and hypertrophy as an outcome of treatment 4,16,18,30,38. Various clinical trials have shown that increasing the frequency and the amplitude of the current are limited by the rapid onset of muscle fatigue and the subject's tolerance to the delivered current, respectively 8,15,25,32. This would sugest that both parameters can not always be used to maximize torque output.…”
Section: Discussionmentioning
confidence: 99%
“…The common neuromuscular adaptations that characterize the aforementioned conditions are muscle weakness and atrophy resulting from disuse or neurological injury 18,38. NMES protocols consist of a combination of pulse parameters and time modulations to induce muscle contractions that aim to simulate both endurance and resistance training 4,10,15,18. The selection of stimulation parameters is typically based on each patient's rehabilitation goals.…”
mentioning
confidence: 99%
See 1 more Smart Citation